This Tujuan dan Pekerjaan Misi Gereja Lokal Masa Kini Berdasarkan Teladan Rasul Paulus Sang Misionaris - Sihombing, Meli Triani; Megawati Manullang (Jurnal Silih Asah, 2025)
This research is motivated by the challenges faced by today's local church in formulating its missionary goals and work amidst rapid social, cultural, and global changes. These changes often make the church's missionary function appear unclear and lack clear direction, putting the church at risk of carrying out its ministry detached from its biblical identity. Therefore, this research aims to reinterpret the local church's missionary goals and work based on the Apostle Paul's example as a missionary, while also proposing its relevance for church ministry in the current context. The research uses a qualitative approach with a literature review method, specifically contemporary missionary theology literature and writings on the Apostle Paul's life and ministry. The results show that, according to Paul, the primary purpose of the church's mission is to educate the congregation through teaching rooted in the truth of the Word, and to bring the congregation into an encounter with Christ through lively worship, expressed in the singing of psalms, praises, spiritual songs, and the celebration of the Lord's Supper. The missionary work exemplified by Paul also includes the proclamation of the Gospel, tangible loving service, empowering the congregation to grow as witnesses of Christ, and social transformation as a manifestation of the church's presence in society. These findings confirm that the local church's mission should not only focus on spiritual aspects, but also be holistic, contextual, and relevant to the needs of the times. Thus, the church is called to develop a mission strategy that is both faithful to the Bible and able to meet the challenges of the modern world, thereby providing a complete witness of God's love for the world.